The Relevance Of The Big Five Model To Students’ Adaptation To The Academic Environment Personality and Academic Experiences - Zanon, Cristian; Araújo, Alexandra; Hutz, Claudio S. (Psico, 2019)
The Big Five has been used as a theoretical framework for the evaluation of the 21stcentury skills and is associated with desirable outcomes. This study evaluates the extent to which the Big Five relates to students’ adaptation to the academic environment. Participants were 845 undergraduate students (60.7% female), aged from 17 to 31 years who answered the Factorial Personality Battery and the Academic Experience Questionnaire. Data reduction analysis at the facet level recovered the Big Five structure and indicated that Extraversion, Neuroticism, and Conscientiousness are, respectively, associated with higher personal, interpersonal, and study related academic adaptation dimensions. Agreeableness and Openness did not cluster with academic dimensions, suggesting lower relevance for academic adaptation in higher education. ***A Relevância do Modelo dos Cinco Grandes Para a Adaptação dos Estudantes ao Ambiente Acadêmico*** O Big Five tem sido usado como referencial teórico para a avaliação das habilidades do século 21 e está associado a resultados desejáveis. Este estudo avalia o quanto os Cinco Grandes Fatores se relacionam com a adaptação dos alunos ao ambiente acadêmico. Participaram 845 estudantes de graduação (60,7% do sexo feminino), com idades entre 17 e 31 anos, que responderam a Bateria de Personalidade Fatorial e o Questionário de Experiência Acadêmica. A análise de redução de dados no nível de faceta recuperou a estrutura dos cinco grandes fatores e indicou que Extroversão, Neuroticismo e Conscienciosidade estão, respectivamente, associados a dimensões de adaptação acadêmica pessoais, interpessoais e relacionadas ao estudo. A Amabilidade e a Abertura não se agruparam com as dimensões acadêmicas, sugerindo menor relevância para a adaptação acadêmica no ensino superior.